Cytoprotection in Multiple Sclerosis and Ischemic Stroke with C-Phycocyanin and Phycocyanobilin - Giselle Pentón-Rol; Javier Marín-Prida; Eduardo Pentón-Arias (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2016)
Cytoprotection in human diseases can be achieved by avoiding and ameliorating tissue damage or by restoring the homeostatic balance either as a local or a systemic defense response. Multiple Sclerosis (MS) and Ischemic Stroke (IS) although being different central nervous system diseases, have common pathogenic aspects such as a deregulated inflammatory response, a toxic redox imbalance and a prominent neuronal dysfunction. C-Phycocyanin (C-PC), the main biliprotein of the Spirulina platensis cyanobacteria, and its associated chromophore named Phycocyanobilin (PCB), has shown strong antioxidant, anti-inflammatory and immunomodulatory properties. In this review, we describe the main experimental findings of our group supporting the medical application of C-PC/PCB as effective diseasemodifying therapies for MS and IS. We demonstrated that C-PC induced regulatory T cells and protected both mice and rats against the progression of experimental autoimmune encephalomyelitis. Both compounds exerted beneficial actions in several models of IS, either in vitro or in vivo. We also addressed the hypothesis of possible combinations of C-PC/PCB with already approved treatments for MS, such as beta IFN, to improve the effectiveness, lower the cost and achieve patient relief or recovery. The safety and tolerability of these compounds are also stressed. The gathered evidence supports the implementation of clinical trials to demonstrate the potential therapeutic effect of C-PC/PCB against these diseases.